The spiny relationship between parallel fibers, climbing fibers, and Purkinje cells - Masoli, Stefano; Rizza, Martina Francesca; Moccia, Francesco; D’Angelo, Egidio (Frontiers in Physiology, 2025)
Cerebellar Purkinje cells are one of the most complex neurons in the central nervous system and are well known for their extensive dendritic tree dotted by dendritic spines. PC spines receive excitatory synapses from parallel and climbing fibers and, although their morphological properties are comparable to those of other neuronal types, they show distinct extracellular and intracellular regulatory properties. Purkinje cell spine protrusion and helical patterning do not require nearby axons, as e.g., in pyramidal cells. Instead, Purkinje cell spines require structural proteins located on parallel and climbing fibers for their stabilisation and maintenance. The total spine number is influenced by scaffold proteins and eventually reflects the total dendritic length and local spine density. Purkinje cell spines were supposed to range up to over 105 in rodents and 106 in humans, but recent experimental data show that spines are less numerous than initially thought. Instead, they are endowed with mechanisms designed to improve their efficiency and differentiation. Some spines are double-headed, thereby enhancing Purkinje cell responses when the companion parallel fiber is stimulated. Other spines are single-headed and presumably endowed with slow neurotransmission mechanisms. Latest experimental data showed that glial cells modulate spines activity after a task or learning. Eventually, these multiple mechanisms can make each spine crucial in its own way for synaptic pattern recognition. In this review, we present the most recent advancements on Purkinje cell spines spanning their biochemical, structural, and functional properties, both in mice and humans, and propose a recalculation of the effective complement of spines and their activation by parallel fibers.